2021
DOI: 10.1590/1984-0462/2021/39/2019190
|View full text |Cite
|
Sign up to set email alerts
|

Pediatricians After Residency: A Survey of Personal/Professional Data and Issues

Abstract: Objective: To assess personal, professional, medical, and scientific educational characteristics and issues reported by pediatricians. Methods: Cross-sectional study based on an online survey including 614 pediatricians who graduated in the last 15 years at a University Pediatric Department in Brazil. Results: The response rate was 331/614(54%). The majority were females (82%), the median age was 33 years (27-40) and median years of pediatric practice was 5 (1-13). High workload (>60 hours/week) occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…The response rate, which was just over 40% of the population of women who used BSR in the state, was considered within the standard for research with online selfadministered questionnaires, as observed in studies that used the same methodology 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response rate, which was just over 40% of the population of women who used BSR in the state, was considered within the standard for research with online selfadministered questionnaires, as observed in studies that used the same methodology 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, there is an increase in the number of undergraduate and graduate women. According to the national census, in 2000, women accounted for 7% of graduate students, but in 2010 this percentage rose to 12.5% 24 . In 2015, 175,419 Brazilian women were enrolled in a graduate program or had a master's or doctoral degree 28 The relationship between breastfeeding and level of education was investigated by different authors [29][30][31] .…”
Section: Discussionmentioning
confidence: 99%
“…They were in a position to inform us on their current learning strategies, but remained close enough to their residency training, thus retaining the ability to make parallel comparisons between their current and previous learning strategies whilst in residency training and provide insights on how residency program assessments may have influenced current SRL. As we were interested in the effects of stakes of assessments in residency training on SRL and its application during clinical practice when participants settled in their new role as ECPs, we deliberately chose to sample up until five years after post-residency training, similar to sampling methods in other studies on ECS [2,24,25,26]. Transition literature has indicated the immediate post-transition period to be an emotionally unnerving experience due to the plethora of new non-clinical skills that these ECS were expected to perform [27,28].…”
Section: Samplementioning
confidence: 99%